Stage-specific expression and divergent functions of two insulinase-like proteases associated with host infectivity in Cryptosporidium. - Yue Huang; Shifeng Pei; Xin Lv; Fuxian Yang; Xiaoqing Gong; Na Li; Yaqiong Guo; Yaoyu Feng; Lihua Xiao (PLoS Neglected Tropical Diseases)
Background The determinants of differences in host infectivity among Cryptosporidium species and subtypes are poorly understood. Results from recent comparative genomic studies suggest that gains and losses of multicopy subtelomeric genes encoding insulinase-like proteases (INS-19 and INS-20 in Cryptosporidium parvum and their orthologs in closely related species) may potentially contribute to these differences. Methodology/principal findings In this study, we investigated the expression and biological function of the INS-19 and INS-20 of C. parvum. CRISPR/Cas9 was used to endogenously tag both genes with the hemagglutinin epitope. Immunofluorescence analysis revealed that INS-19 and INS-20 are expressed at different developmental stages of the pathogen. Although knockout of either had no detectable effect on the in vitro growth of C. parvum, knockout of INS-20, deletion of its multiple domains, or mutation of the active motif in the functional domain reduced the intensity of C. parvum infection in IFN-γ knockout mice. Consistent with this, mice infected with the INS-20-deleted mutant had reduced intestinal damage and parasite burden. Conclusions/significance These results suggest that INS-19 and INS-20 have stage-specific expression with distinct biological functions, and that the presence of the INS-20 in zoonotic C. parvum contributes to its infectivity and fitness in mice.